INTEGRATING MAHABBAH VALUES INTO THE CURRICULUM OF LOVE: A NEW PARADIGM FOR CHARACTER BUILDING (AKHLAKUL KARIMAH) IN ISLAMIC ELEMENTARY SCHOOLS (MADRASAH IBTIDAIYAH) - Ernawati Ernawati; Herlina Herlina; Wiwi Uswatiyah (Sekolah Tinggi Agama Islam Al Hidayah, 2026)
Contemporary Islamic education is often trapped in cognitive formalism that ignores the affective dimension, thus failing to form students' characters authentically. This study aims to analyze the strategy for integrating Mahabbah (love) values within the